2017
DOI: 10.4236/fns.2017.85037
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Organoleptical and Quality Characteristics of Gluten-Free Rice Cakes Formulated with Sorghum and Germinated Chickpea Flours

Abstract: Gluten-free bakery products are produced for people suffering from celiac disease due to sensitivity to gluten. So, the aim of this work was to study the effect of partial substitution of rice flour at 20%, 30% and 40% with sorghum and germinated chickpea flours on rheological, physical, sensory properties and staling rate of prepared gluten-free cake. Obtained results showed that germinated chickpea flour had the highest contents of crude protein (23.62%), lipids (4.89%) and crude fibers (5.76%) as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
2
11
0
3
Order By: Relevance
“…Soybean meal presented the highest ash concentration, 6.3%, value consistent with those previously reported of circa 6.29% (Raya-Pérez, Aguirre-Mancilla, Tapia-Aparicio, Ramírez-Pimentel, & Covarrubias-Prieto, 2012). For chickpea flour, ash content was 2.9%, results similar to those previously reported of 2.79% -3.1% (Gadallah, 2017;Wani & Kumar, 2014).…”
Section: Resultssupporting
confidence: 90%
“…Soybean meal presented the highest ash concentration, 6.3%, value consistent with those previously reported of circa 6.29% (Raya-Pérez, Aguirre-Mancilla, Tapia-Aparicio, Ramírez-Pimentel, & Covarrubias-Prieto, 2012). For chickpea flour, ash content was 2.9%, results similar to those previously reported of 2.79% -3.1% (Gadallah, 2017;Wani & Kumar, 2014).…”
Section: Resultssupporting
confidence: 90%
“…Vanillia 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0. The results of chemical composition of white rice flour were in line with confirmed those of Qin et al (2016) and Gadallah (2017). The chemical composition of white corn flour was in harmony with those of Gwirtz and Garcia-Casal (2014).…”
Section: Discussionsupporting
confidence: 76%
“…Chickpea flour has also been used in the formulation of biscuits based on rice, potato, and corn flours (Ergin and Herken, 2012). More recently, some studies have proposed germinated chickpea flour to supplement rice and sorghum flours in the formulation of gluten-free cakes (Gadallah, 2017). Sarabhai et al (2017) have also studied the potential use of gluten-free flours based on amaranth and chickpea in the biscuit-making process.…”
Section: Introductionmentioning
confidence: 99%
“…Devisetti et al (2015) proposed proso millet flour with added gum acacia, guar, XG, HPMC, and CMC to formulate a gluten-free cookie. Other research was reported into the use of composite gluten-free flours, such as rice-cassava flour, with incorporated XG in flat bread and biscuit production (Aly Mona and Seleem Hinar, 2015) and rice-sorghum-chickpea flour with added XG in gluten-free cakes (Gadallah, 2017). Sarabhai et al (2017) have studied the biscuit-making potential of amaranth-puffed chickpea composite flour with added gum arabic, carrageenan, and HPMC.…”
Section: Introductionmentioning
confidence: 99%